What can be the Role of Public-Private Partnerships and the role of the Collective Action in Ensuring Sustainable Smallholder Participation in High Value Fruit and Vegetable Supply Chains in Albania? - SULI, Hergys; BOMBAJ, Florjan; XHABIJA, Gjergj; SULI, Dudi (European Journal of Sustainable Development, 2013)
Albania is a Mediterranean country where fruitsand vegetables occupy an important placein the cropping systems practiced by theAlbanian farms but also in the foodconsumption of the population. Today, the fruits and vegetables growers in Albania havelow production capacity and difficulties inselling their products on national and regionalmarket. These poor producers face problems ofhow to produce safe food (World Bank2007), be recognized as producing safe food, identify cost-effective technologies forreducing risk, and be competitive with larger producers with advantage of economies ofscale in compliance with food safety requirements. In enabling the smallholders to remaincompetitive in such a system, new institutional arrangements are required. The new andemerging food system (dominated by domestic urban market and export markets,regional competitiveness, globalization, etc.) with high demands for compliance with foodsafety and traceability disfavor the smallholders due tohigh coordination costs. Theproblem is exacerbated by geographic dispersion, low education, and poor access tocapital and information (Poulton 2005; Humphrey 2005; Rich and Narrod 2005). Themain idea of this paper is that the public-private partnerships can play a key role increating farm to fork linkages that can satisfy the market demands for food safety whileretaining smallholders in the supply chain. Our big question is “how this can be possiblein Albania and which are the rightpolicies to forward this idea?